The Complete Idiot's Guide To the Sun - Pasachoff, Jay M; Edited by Chisbolm, Jennifer (USA Alpha, 2003)
At the center of our solar system, the sun has long been a popular object of curiosity and study throughout human history. Stonehenge may have been built primarily to observe it. The Mayans designed their mathematically sophisticated calendars around it. And, Galileo nearly came to blows with other keen minds in describing its unique features.
Include Colored Pictures,Graph, Indexes
Keywords: Sun -- Solar activity -- Idiot`s Guide